Antimicrobial Activity of Phytic Acid: An Emerging Agent in Endodontics - Nassar, Rania; Nassar, Mohannad; Vianna, Morgana E.; Naidoo, Nerissa; Alqutami, Fatma; Kaklamanos, Eleftherios G.; Senok, Abiola; Williams, David (Frontiers in Cellular and Infection Microbiology, 2021)
Background Phytic acid (IP6) is a promising and emerging agent, and because of its unique structure and distinctive properties, it lends itself to several applications in dentistry. Recently, IP6 was proposed as a potential chelating agent in endodontics. However, there is limited knowledge regarding its antimicrobial and antibiofilm effectiveness. The aims of this study, were therefore to evaluate the antimicrobial and antibiofilm activities of IP6 against a range of microbial species and compare these with ethylenediaminetetraacetic acid (EDTA) and sodium hypochlorite (NaOCl). The contact time required for IP6 to exert its bactericidal effect on Enterococcus faecalis was also determined. Methods The inhibitory and biocidal activities of IP6, EDTA and NaOCl were assessed using a broth microdilution assay against 11 clinical and reference strains of bacteria and a reference strain of Candida albicans. The contact time required for various IP6 concentrations to eliminate planktonic cultures of E. faecalis was determined using a membrane filtration method according to BS-EN-1040:2005. IP6 bactericidal activity was also evaluated using fluorescent microscopy, and the antibiofilm activity of the test agents was also determined. Results IP6 was biocidal against all tested microorganisms. At concentrations of 0.5%, 1% and 2%, IP6 required 5 min to exert a bactericidal effect on E. faecalis, while 5% IP6 was bactericidal after 30 s. IP6 also eradicated biofilms of the tested microorganisms. In conclusion, IP6 had notable antimicrobial effects on planktonic and biofilm cultures and exhibited rapid bactericidal effects on E. faecalis. This research highlighted, for the first time the antimicrobial and antibiofilm properties of IP6, which could be exploited, not only in dental applications, but also other fields where novel strategies to counter antimicrobial resistance are required.